Viability of calcifying bacterial formulations in fly ash for applications in building materials - Dhami, N.; Mukherjee, Abhijit; Reddy, M. (Springer Link, 2013)
Evidence of bacterial involvement in precipitation of calcium carbonates has brought a revolution in the field of applied microbiology, geotechnical sciences, environmental and civil engineering with its marked success in restoration of various building materials. For applications of these calcite binder-producing bacterial cultures, different expensive carrier materials have been used but their high costs have come in the way of their successful commercialization. In the present study, we have explored the potential of cheap industrial by-product fly ash as a carrier material for bacterial cells and investigated the viability of calcifying bacterial isolates: Bacillus megaterium, Bacillus cereus, and Lysinibacillus fusiformis in fly ash carrier at varying temperatures and moisture conditions along with biomineralization efficacy of these formulations. We used laser scanning confocal microscopy to analyze the viability of bacteria by florescent dye 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) along with the plate count method. Results revealed that fly ash successfully served as an effective carrier material and bacterial formulations stored at 4 °C provided longer shelf life than those stored at higher temperatures. Up to 106 cfu/g was found to sustain in all formulations at 4 °C compared to 104-105 cfu/g in case of higher temperatures up to 1 year. For 4 °C, higher moistures (50 %) were found to provide better survivability while for higher temperatures, lower moistures (30 %) favored higher viability. The biomineralization capability of fresh and formulated bacterial cells was compared on the basis of precipitation of carbonates and it was found that carbonate precipitation efficacy of formulated bacterial cells was comparable to fresh bacterial cells.